Evaluating CPI and SPI Indicators in Project Management Maturity Evolution - Gomes, Luciana de Q. Leal; Gomes, Reinaldo C. M.; M. Gomes de Gusmão, Cristine; Perrelli de Moura, Hermano (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2013)
Project management has become a common subject in Software Engineering and an everyday task in software organizations. In this task, the effective use of technologies can determine the success of any business; affect quality and ability to provide products and services on time. According to some authors, success in project execution can be associated with organization maturity. Organizations search for project management maturity in order to improve their management process and increase client satisfaction. Maturity is related to cost, time and quality, and can determine the success of projects. In the context of project management, we have two important indicators: Schedule Performance Indicator (SPI) and Cost Performance Indicator (CPI). SPI indicates whether the budgeted costs for work scheduled to date exceed the budgeted costs for the work performed to date. CPI indicates whether the actual costs for the work performed to date exceed the budgeted costs for the work performed to date. These indicators give information about whether or not the project is on track, so they are important factors which represent success in project management. This paper discusses how Cost/Schedule Performance Indicators are related to project management maturity and presents the results based on IT professionals’ opinion analysis.